PENGARUH PERMAINAN TRADISIONAL BAKIAK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK NURUL HUDA PEKANBARU - Eliza Eka Putri; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research is aimed to (1) to know the children’s hard motoric before apply traditional game bakiak of children age 5-6 years in TK Nurul Huda Pekanbaru. (2) to know the children’s hard motoric after apply traditional game bakiak of children age 5-6 years in TK Nurul Huda Pekanbaru. (3) to know bigness of influence skill hard motoric after apply traditional game bakiak of children age 5-6 years in TK Nurul Huda Pekanbaru.The population in this study that children age 5-6 years totaling 22 children and sample in this study amounted to 22 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation. So the result of this research were (1) the ability of hard motoric children’s age 5-6 years before apply traditional game bakiak include low. (2) the ability of hard motoric children’s age 5-6 years after apply traditional game bakiak increase and appertain high, means there was increasing of children hard motoric ability after this traditional game was done. In this traditional game each part of body is moved. (3) there was significant influence in traditional game bakiak toward hard motoric ability of children age 5-6 years of TK Nurul Huda Pekanbaru as 40,7 %.Keywords: Traditional Game, Hard Motoric